Effects of in vitro endochondral priming and pre-vascularisation of human MSC cellular aggregates in vivo. Issue 1 (December 2015) - Freeman, Fiona; Allen, Ashley; Stevens, Hazel; Guldberg, Robert; McNamara, Laoise
Abstract Introduction During endochondral ossification, both the production of a cartilage template and the subsequent vascularisation of that template are essential precursors to bone tissue formation. Recent studies have found the application of both chondrogenic and vascular priming of mesenchymal stem cells (MSCs) enhanced the mineralisation potential of MSCs in vitro whilst also allowing for immature vessel formation. However, the in vivo viability, vascularisation and mineralisation potential of MSC aggregates that have been pre-conditioned in vitro by a combination of chondrogenic and vascular priming, has yet to be established. In this study, we test the hypothesis that a tissue regeneration approach that incorporates both chondrogenic priming of MSCs, to first form a cartilage template, and subsequent pre-vascularisation of the cartilage constructs, by co-culture with human umbilical vein endothelial cells (HUVECs) in vitro, will improve vessel infiltration and thus mineral formation once implanted in vivo. Methods Human MSCs were chondrogenically primed for 21 days, after which they were co-cultured with MSCs and HUVECs and cultured in endothelial growth medium for another 21 days. These aggregates were then implanted subcutaneously in nude rats for 4 weeks. We used a combination of bioluminescent imaging, microcomputed tomography, histology (Masson's trichrome and Alizarin Red) and immunohistochemistry (CD31, CD146, and α-smooth actin) to assess the vascularisation and mineralisation potential of these MSC aggregates in vivo. Results Pre-vascularised cartilaginous aggregates were found to have mature endogenous vessels (indicated by α-smooth muscle actin walls and erythrocytes) after 4 weeks subcutaneous implantation, and also viable human MSCs (detected by bioluminescent imaging) 21 days after subcutaneous implantation. In contrast, aggregates that were not pre-vascularised had no vessels within the aggregate interior and human MSCs did not remain viable beyond 14 days. Interestingly, the pre-vascularised cartilaginous aggregates were also the only group to have mineralised nodules within the cellular aggregates, whereas mineralisation occurred in the alginate surrounding the aggregates for all other groups. Conclusions Taken together these results indicate that a combined chondrogenic priming and pre-vascularisation approach for in vitro culture of MSC aggregates shows enhanced vessel formation and increased mineralisation within the cellular aggregate when implanted subcutaneously in vivo.